BIMG-09. GLUTAMINE AND GLYCINE BY MR SPECTROSCOPY IDENTIFY AGGRESSIVE GLIOMAS. (25th March 2021) - Choi, Changho; Askari, Pegah; Daoud, Elena; Hatanpaa, Kimmo; Raisanen, Jack; Levy, Michael; Pan, Edward; Patel, Toral; Mickey, Bruce; Maher, Elizabeth
Abstract: Cancers reprogram their metabolism and the resulting alterations in metabolite abundance can be monitored in patients noninvasively using proton magnetic resonance spectroscopy (MRS). We evaluated glutamine, glycine and 2-hydroxyglutarate (2HG) in 27 adult subjects with gliomas (17 male and 10 female; age 22 - 69, median 39 years) using optimized MRS at 3T (PRESS TE 97ms) and examined their association with post-gadolinium enhancement, cell proliferation rate (MIB-1 labeling index), and overall survival of patients. The tumors included 9 glioblastomas (3 IDH mutated and 6 IDH wildtype), 10 astrocytomas (7 IDH mutated and 3 IDH wildtype), and 8 oligodendrogliomas (IDH mutated). The concentrations of glutamine and glycine were both significantly higher in enhancing tumors than in non-enhancing tumors (p=0.001 and 0.0001, respectively). The concentrations of glutamine and glycine were both positively correlated with MIB-1 (p=4E-5 and 1E-7, respectively). The sum of glutamine and glycine levels showed stronger association with MIB-1 (p=5E-10, r=0.89). In the Kaplan-Meier overall survival analysis, the survival was significantly shorter in patients with glutamine levels higher than 4.1 mM than those with concentrations less than 4.1 mM (p=0.02). For glycine, the patients with higher than 2.4 mM showed association with poor survival (p=0.03). The sum of glutamine and glycine levels showed stronger association with overall survival (p=0.008, cutoff 8.5mM). 2HG level greater than 0.5 mM was associated with long survival (p=0.01). We tested metabolic ratios to 2HG, in which 2HG estimates less than 1 mM were put as 1 mM (avoiding infinite ratios arising from null 2HG cases). The glutamine/2HG, glycine/2HG, and (glutamine+glycine)/2HG showed strong association with overall survival (p=2E-4, 2E-5 and 4.5E-7, respectively). Our data suggest that increased metabolism of glutamine and glycine is closely associated with rapid cell proliferation and poor survival, suggesting the metabolites are imaging biomarkers of glioma aggressiveness.